Penyuluhan dan Pelatihan Pembuatan Pudding Daun Kelor sebagai Inovasi Pangan Bernutrisi bagi Masyarakat Desa Bintana - Hendrik David Julianus Borolla; Juliana Juliana (Solusi Bersama : Jurnal Pengabdian dan Kesejahteraan Masyarakat, 2025)
Counseling and training on making moringa leaf pudding in Bintana Village aims to increase public awareness of the nutritional benefits of moringa leaves and provide skills in processing them into innovative food products. Moringa leaves are known to be rich in nutrients and antioxidants that are beneficial for health. This activity involves education on the nutritional content of moringa leaves, demonstrations of making pudding, and hands-on practice sessions by participants. The results of the activity showed that the community has a high interest in adopting the innovation of utilizing moringa leaves as an alternative to healthy food. In addition, taste evaluations showed that moringa leaf pudding was well received. It is hoped that this innovation can increase consumption of healthy food and encourage the use of local plants in food diversification.